Development models and method of forming cascade mac using modular transformation - Король, Ольга Григорівна; Пархуць, Любомир Теодорович; Євсеєв, Сергій Петрович (Ukrainian Information Security Research Journal, 2013)
To construct the MAC codes satisfying collision properties of universal hash functions are used algorithms with modular transformations that provide provably secure hashing information. The disadvantages of such algorithms is the high computational complexity and low rate of formation of the hashes, which significantly reduces the scope of their application. The choice of cycle functions in the scheme provably secure key universal hashing, a model and a method of forming code integrity and authenticity of data based on the modular transformation algorithm to reduce the computational complexity of the hashing scheme using cyclic functions. The developed method of cascade formation of MAC provides the required performance properties of universal hash collision, demonstrable resilience and high speed forming a hash code.